2016
DOI: 10.1038/srep21004
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal phthalate ester exposure induced placental MTs, FATP1 and HFABP mRNA expression in two districts of southeast China

Abstract: Plastic production releases phthalate esters (PAEs), which can alter the expression of metallothioneins (MTs), fatty acid transport protein 1 (FATP1) and heart fatty acid binding protein (HFABP). A total of 187 mother-infant pairs were recruited, 127 from Chenghai (high exposed group) and 60 from Haojiang (low exposed group), to investigate the association between neonatal PAE exposure and mRNA expression of placental MTs, FATP1 and HFABP. Umbilical cord blood and placenta samples were collected for measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Maternal whole blood sample was drawn using 6mL Vacutainer tubes containing 10.8 mg of K2-EDTA (dipotassium-ethylene diaminetetraacetic acid) as an anticoagulant and stored at -20°C (47). Umbilical cord blood was collected shortly after delivery with an EDTA- containing tube and stored at −20°C (39, 48, 49). Maternal urine samples were collected in the morning into polypropylene conical centrifuge tubes during the hospital stay (50).…”
Section: Methodsmentioning
confidence: 99%
“…Maternal whole blood sample was drawn using 6mL Vacutainer tubes containing 10.8 mg of K2-EDTA (dipotassium-ethylene diaminetetraacetic acid) as an anticoagulant and stored at -20°C (47). Umbilical cord blood was collected shortly after delivery with an EDTA- containing tube and stored at −20°C (39, 48, 49). Maternal urine samples were collected in the morning into polypropylene conical centrifuge tubes during the hospital stay (50).…”
Section: Methodsmentioning
confidence: 99%
“…This study showed that dimethyl phthalate (DMP) and diethyl phthalate (DEP) did not differ by sex in their associations with any genes tested. However, DEHP was associated with MT and MT-2A only in female placentas [ 50 ]. While this study highlights the importance of considering placental/fetal sex, several factors must be taken into account when interpreting these findings.…”
Section: Sex-specific Placental Outcomesmentioning
confidence: 99%
“…Di-(2-ethylhexyl)-phthalate (DEHP) is the most widely-used phthalate, and is listed as a priority hazardous substance by the European Community, the United States Environmental Protection Agency, and the China National Environmental Monitoring Center [ 7 , 8 ]. Previous studies showed that DEHP and its dominant metabolites, mono (2-ethylehxyl) phthalate (MEHP) and phthalic acid (PA), the major intermediate degradation products of most PAEs (including DEHP), produce adverse developmental, neurological, respiratory, and immune effects in humans [ 4 , 9 , 10 , 11 , 12 , 13 ]. Therefore, discovering efficient DEHP degraders with high environmental persistence and wide availability is urgently required, as is establishing remediation strategies to eliminate DEHP and its metabolites from the environment.…”
Section: Introductionmentioning
confidence: 99%